2009
DOI: 10.1111/j.1600-0404.1985.tb03218.x
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of multiple sclerosis in the county of Hordaland, Western Norway

Abstract: We studied the distribution of MS cases in the county of Hordaland, Western Norway. The total MS population comprised 426 patients.The prevalence on January lst, 1963, and on January lst, 1983, and the average annual incidence in the period 1963-1982 were all lower in thescoastal area compared to the inland area.An increase in incidence started in the urban area and was followed some 10 years later in the rural area.The Knox method revealed no statistically significant evidence of clustering either for time/pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The study also showed an uneven geographical distribution, with a gradient in prevalence decreasing from the eastern mountainous part of the region to the western areas closer to the coast. This is in line with other studies conducted at different latitudes, showing lower MS incidence in the coastal area compared to the inland area [ 32 , 33 ]. Diet and lifestyle factors have been hypothesized to modulate the risk of MS across regions at the similar latitude.…”
Section: Discussionsupporting
confidence: 93%
“…The study also showed an uneven geographical distribution, with a gradient in prevalence decreasing from the eastern mountainous part of the region to the western areas closer to the coast. This is in line with other studies conducted at different latitudes, showing lower MS incidence in the coastal area compared to the inland area [ 32 , 33 ]. Diet and lifestyle factors have been hypothesized to modulate the risk of MS across regions at the similar latitude.…”
Section: Discussionsupporting
confidence: 93%
“…In Hordaland, also in coastal northwestern Norway, the mean annual incidence of MS was 2.5 per 100,000 population in 1958–1962 and the prevalence was 20 per 100,000 population on January 1, 1963 13 . The prevalence in Hordaland in 1963–1982 was also clustered and lower in the coastal area than in the inland area 14 .…”
Section: Resultsmentioning
confidence: 91%
“…The incidence of MS in Hordaland County has in previous studies increased from 0.2/100 000 in 1935, 10 to 0.67/100 000 in 1951 11 and to 4.7/100 000 in 1978–1982. 9 However, in the present long-term follow-up study, we also identified patients with disease onset years prior and thus higher incidence rates of 1.8/100 000 during 1953–1957, 6.9/100 000 during 1978–1982 followed by a stable high level of approximately 7–8/100 000 during later years.…”
Section: Discussionmentioning
confidence: 87%